2020
DOI: 10.1177/0269216320974262
|View full text |Cite
|
Sign up to set email alerts
|

End of life care for long-term neurological conditions: A meta-ethnographic review of the experiences of informal carers

Abstract: Background: Family and friends are key providers of care for people living with a long-term neurological condition. Neurological conditions are a significant global contributor to disability and premature death. However, previous research suggests carers often struggle to access appropriate support at end of life. Aims: This review sought to synthesise qualitative studies discussing end-of-life and palliative issues for informal carers supporting people living with neurological conditions. Design: This was a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…The guidelines of the European Federation of Neurological Societies (EFNS) have underlined this point, stressing that ACP should be discussed early with the patient and CGs while respecting the patient’s social and cultural background [ 14 ]. According to our findings, “early” or “soon” did not mean “immediately”, but rather “appropriate” for the patients/CGs system, and this highlights what has been conceptualized elsewhere [ 37 ] as the “importance of sensitive and timely conveyance of information”. In other words, there is a need to assess the readiness of individuals with ALS and their CGs to have this conversation [ 50 ].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The guidelines of the European Federation of Neurological Societies (EFNS) have underlined this point, stressing that ACP should be discussed early with the patient and CGs while respecting the patient’s social and cultural background [ 14 ]. According to our findings, “early” or “soon” did not mean “immediately”, but rather “appropriate” for the patients/CGs system, and this highlights what has been conceptualized elsewhere [ 37 ] as the “importance of sensitive and timely conveyance of information”. In other words, there is a need to assess the readiness of individuals with ALS and their CGs to have this conversation [ 50 ].…”
Section: Discussionsupporting
confidence: 53%
“…In this regard, there is a need to improve communication between HPs and individuals with ALS/CGs by recognizing that the time needed for acceptance of the diagnosis by individuals with ALS/CGs can differ, as can the coping strategies they adopt [ 27 , 37 ]. At the same time, diagnosis communication is difficult for HPs [ 38 ], whose communication skills come into play and who need improvement [ 39 , 40 ] and effective training programs [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complex nature of the palliative care sector, which can be difficult to navigate, can also deter patients, families and carers from seeking palliative care, or may leave them at a loss regarding how to best access and arrange the support and professional help they need [ 34 ]. The carers of patients with MND in this study and others have reported that they find themselves lost in a “service provision maze”, and do not know who to approach for support when needed [ 10 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have highlighted that healthcare professionals frequently overlook caregivers' need for support [55,56]. Additionally, information regarding prognosis and disease progression is often inconsistent or inadequate [19], a situation exacerbated by the absence of a shared language regarding death in contemporary society [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…In the face of heightened burden, family caregivers frequently find themselves compelled to cut down on the time and attention they allocate to their personal needs, leisure pursuits, and broader family and social connections [18,19]. The rising demand for caregiving often necessitates leaving employment or scaling back working hours, leading to reduced income and limited career prospects [20].…”
Section: Introductionmentioning
confidence: 99%